PPO.28 Birth prevalence and one year survival of congenital diaphragmatic hernia, England and Wales, 2002–2011. (9th June 2014) - Springett, A; Draper, ES; Rankin, J; Rounding, C; Tucker, D; Wellesley, D; Wreyford, B; Morris, JK
Abstract : Background: Congenital diaphragmatic hernia (CDH) is the failure of the diaphragm to develop and fuse properly during fetal development, allowing the abdominal organs to push up into the chest cavity. Newborn infants with CDH often have severe respiratory distress which can be life-threatening unless treated appropriately. The aim of this study was to determine the birth prevalence, characteristics, antenatal diagnosis, pregnancy outcome and survival of cases with CDH. Methods: Six regional congenital anomaly registers (covering 36% of births in England and Wales) from 2002–2011 contributed 743 cases to this study. Results: The overall birth prevalence of CDH was 3.4 (95% CI: 3.1–3.6) per 10, 000 births; there was no significant change in the birth prevalence over the ten years. Sixty-one percent were isolated, 27% were associated with another structural anomaly (multiple) and 12% had a chromosomal anomaly (36% Edwards, 9% Patau syndrome). Sixty-six percent of isolated, 80% of multiple and 83% of chromosomal CDH cases were antenatally diagnosed. The majority of cases with isolated and multiple CDH were live born (84% and 62% respectively), whereas 58% of CDH pregnancies associated with a chromosomal anomaly ended in a termination (58%). The 1-year survival of live born babies was higher in isolated CDH (75%) compared to multiple (64%) and chromosomal CDH cases (57%). Conclusions: The prevalence of CDH remained constant over the past 10 years. Sixty-one percent of CDH cases were isolated, of whom 66% were antenatally diagnosed. One-year survival in isolated cases was only 75%.